Selection index and agronomic characters of doubled haploid rice lines from anther culture - WIRA HADIANTO; BAMBANG SAPTA PURWOKO; ISWARI SARASWATI DEWI; WILLY BAYUARDI SUWARNO; PURNAMA HIDAYAT (Society for Indonesian Biodiversity, 2023)
Abstract. Hadianto W, Purwoko BS, Dewi IS, Suwarno WB, Hidayat P. 2023. Selection index and agronomic characters of doubled haploid rice lines from anther culture. Biodiversitas 24: 1511-1517. Development of superior rice varieties requires selection of the best lines having good agronomic characters and high yields. This study aimed to select high-yielding doubled haploid rice lines obtained from anther culture through index selection and agronomic characters. The study was conducted using a single-factor randomized complete block design (RCBD) with genotype as treatment. Sixty doubled haploid lines and 5 check varieties were evaluated along with three replications, hence, the total experimental unit was 195. Analysis of variance showed that the genotypes had a significant effect on all observed characters, except for the number of productive tillers. The agronomic characters observed had a high broad sense of heritability, except for the number of productive tillers which was in the medium category. Furthermore, index selection was carried out based on productivity, the number of productive tillers, the total number of grains, as well as the percentage of filled grains. Based on the index selection, 29 lines were selected among the 60 doubled haploid rice lines tested. These lines had the range in productivity from 2.95 to 6.77 ton ha-1, the number of productive tillers from 12.3 to 20.8 tillers, the total number of grains from 135 to 275.4 seeds, the filled grain percentage from 53.23 to 87.61%, and the selection index from -1.48 to 7.88. The selected lines will be further tested at the next experimental stage in several locations to produce high-yielding, brown planthopper-resistant, and drought-tolerant rice varieties.